Project Management Is an Industry with High Barriers to Entry: A Case Study - Anna STASIUK-PIEKARSKA; Artur WŁODARCZYK (Communications of International Proceedings, 2021)
Aim: The aim of the paper is to outline issues encountered in project management in the context of risk management in the ceramic sanitaryware industry. The authors consider the industry to be one characterized by high barriers to entry, which distinguishes its project management approach from those commonly described in the literature. Research method: The authors base their considerations on a literature review, participant observations and an analysis of relevant company documents. The article relies on a case study constituting preliminary research conducted for the purposes of a project of the Faculty of Management Engineering of the Poznań University of Technology (No. 0811/SBAD/1015). Conclusions: The authors are of the view that by focusing on the common elements of project management and systems engineering, they can identify not only the opportunities to structure project activities but also those to improve them. In striving to gain a competitive advantage, businesses make numerous improvements aimed at reducing operating expenses and boosting efficiency. However, it is recognized that many such changes are not systemic, and that many of the decisions being made are poorly informed.
Keywords: Project management; systems engineering; industries with high barriers to entry; ceramic sanitaryware industry